Visionary Leadership of The Head of Diniyah Madrasah in Improving The Quality Santri - Muhammad Amin Fathih; Triyo Supriyatno; Muhammad Amin Nur (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
This article aims to analyze: 1) the concept of the visionary leadership of the head of Madin (Madrasah Diniyah) in improving the quality of students (santri) at the Al-Khoirot Islamic boarding school, 2) the process of the relationship between the head of Madin and its members in improving the quality of students at the Al-Khoirot Islamic boarding school, 3) the results of achieving the quality of students carried out by the head of Madin Al-Khoirot. This article uses a qualitative approach with the type of case study. The data collection technique is done by interview, observation, and documentation. While the data analysis uses data condensation, display data, and make conclusions. The results showed: 1) The concept of the visionary leadership of the Madin Al-Khoirot head includes: a) the formulation of the vision based on the provisions of Madin graduates. b) make changes and innovations that advance. c) conduct training and monitoring of Madin teachers. d) build cooperation with pesantren. 2) the process of building good relations is carried out by holding regular meetings with all Madin residents. 3) the results of quality achievement are shown by the success of Madin Al-Khoirot graduates being accepted in foreign Islamic educational institutions.